Lightweight energy-absorbing polyurethane power battery pouring sealant as well as preparation method and application thereof

By using a liquid MDI and polythexide amuiol to prepare polyurethane prefabricated, and react with 1,4-butanol reactions to generate microporous polyethait, solve the aspect of power battery irrigation and sealing Insufficient, the comprehensive performance of polyurethane power batteries is excellent and simple and environmentally friendly.

CN119351035AActive Publication Date: 2025-01-24SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411450686.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The existing power battery potting glue has shortcomings in lightweight, shock-absorbing and energy-absorbing performance, and the preparation process is complex, the mass-volume ratio is large, and the thermal stability and shock-absorbing performance need to be improved.

Method used

The polyurethane pre-polyette with liquid MDI and polythexoluxol is used to prepare the end of isocyanate group for the raw material, and then the micro-pore foam polyurethane is reacted to generate microporous polyurethane by adjusting the expansion coefficient with 1,4-butanol to prepare lightweight absorbent polyurethane power batteries. Irrigation.

Benefits of technology

The lightweight, energy -absorbing shock absorption performance, mechanical performance, thermal stability and adhesion performance of polyurethane power battery irrigation sealing are realized, and the preparation process is simple, controllable, environmentally friendly, reliable, and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351035A_ABST
    Figure CN119351035A_ABST
Patent Text Reader

Abstract

The invention discloses a light-weight energy-absorbing polyurethane power battery pouring sealant and a preparation method and application thereof.The preparation method comprises the steps that liquid MDI and polytetrahydrofuran glycol serve as raw materials to prepare an isocyanate-terminated polyurethane prepolymer; the polyurethane power battery pouring sealant is prepared by reacting 1, 4-butanediol through adjusting a chain extension coefficient to generate microcellular foaming polyurethane, and a microcellular structure is formed through the reaction, so that the related performance requirements of light weight, energy absorption and the like of the power battery pouring sealant are met; the polyurethane pouring sealant prepared by the invention has the advantages of light weight, and excellent energy absorption and vibration reduction performance, mechanical property, thermal stability and bonding performance; and the preparation process is simple and controllable, environment-friendly and reliable, the cost is low, the stability and safety of the power battery can be improved, the development of new energy automobiles is promoted, and the environment-friendly requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials and relates to a polyurethane potting compound, and in particular to a lightweight energy-absorbing polyurethane power battery potting compound and a preparation method and application thereof. Background Art

[0002] With the implementation of automobile environmental protection plans in various countries, the production and sales of new energy vehicles will continue to increase rapidly, and the market scale will continue to expand. The development of new energy vehicles is conducive to solving energy and environmental problems, freeing automobiles from dependence on oil, and is expected to become the main direction of future development of the automobile industry. The overall performance of new energy vehicles depends to a large extent on the performance of their motors, power batteries and electronic controls. As one of the core components of new energy vehicles, power batteries have extremely high requirements for their various performances. As one of the key materials of power batteries, power battery potting glue is used to protect the internal structure of power batteries and prevent internal leakage. With the continuous development and progress of battery technology for new energy vehicles, the requirements for lightweight, shock absorption and energy absorption performance of power battery potting glue are also getting higher and higher.

[0003] Lithium batteries have unique advantages such as high voltage, high energy density, long cycle life, energy saving and environmental protection. They are widely used in new energy vehicles, namely high-voltage power batteries. In addition to high requirements for flame retardancy and thermal conductivity, weight reduction is also crucial for new energy vehicles in order to maximize the mileage within a given battery. Lightweighting of electric vehicles has become an inevitable trend in the future development of new energy vehicle technology, so power battery potting glue also needs to be lightweight. In the car battery panel, there are many single battery packs composed of lithium batteries, which form a battery pack, and then the battery pack forms a battery panel. Under high-speed operation, the car will inevitably be bumpy, and the battery will shake severely and vibrate. Therefore, the potting glue needs to have good shock absorption and adhesion, etc., to achieve organic interaction with the polar groups on the surface of the battery shell plastic and aluminum parts, so as to give full play to the advantages of adhesion and stability.

[0004] Potting glue is usually used for bonding, sealing and coating protection of power batteries, and is an indispensable part of protecting power batteries. At present, there are three types of power battery potting glue widely used in the market: epoxy resin, silicone and polyurethane. Epoxy resin potting glue has the advantages of high temperature resistance, good adhesion, and excellent electrical insulation ability, but it has disadvantages such as poor toughness, easy cracking due to cold and hot shock, and poor resistance to moisture and heat. It is mostly used for sealing electronic components in the fields of transformers, capacitors, and drive power supplies. Silicone potting glue has good weather resistance, a wide operating temperature range, no cracking, and excellent waterproof and seismic resistance, but it has disadvantages such as low bonding strength, low strength, and poor tear resistance. It is not easy to keep the battery fixed after being squeezed, causing power battery failure.

[0005] Polyurethane potting glue has the characteristics of adjustable hardness, wide strength range, adjustable modulus, high elasticity, high impact resistance, high wear resistance, high adhesion and excellent low temperature resistance. Combined with the design of power battery packs, polyurethane potting glue can better match the bonding and thermal conductivity of battery cells, and is increasingly widely used in new energy batteries. Polyurethane has attracted much attention and is widely used because of its unique structural characteristics, which can well overcome the shortcomings of epoxy resin brittleness and low mechanical strength and poor bonding performance of silicone resin. Polyurethane potting glue is mainly composed of additives such as isocyanate and polyol, filler, chain extender, catalyst and foam leveling agent. After curing, multiple urethane bonds (-NHCOO-) are formed, and the soft and hard segments are arranged alternately to form a repeated structural unit. Isocyanate provides mechanical strength as a hard segment, and polyol provides elasticity as a soft segment, making the sealant both strong and elastic. Commonly used isocyanate products include: toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI, such as MDI-100 and MDI-50), polymethylene polyphenyl isocyanate (PAPI, such as PM-200), isophorone diisocyanate (IPDI) and modified MDI (liquefied MDI), among which MDI, TDI and PAPI are widely used in the production of polyurethane potting adhesives. Oligomer polyols are basically divided into oligomer polyols such as terminal hydroxyl polybutadiene (HTPB), polyether polyols (such as polytetramethylene glycol), polyester polyols (such as polyethylene adipate glycol) and castor oil. Castor oil, in particular, is now widely used in the production of potting adhesives. The existing polyurethane potting adhesive has a complex preparation process, a large mass-to-volume ratio, and its thermal stability, shock absorption and energy absorption properties still need to be improved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a lightweight energy-absorbing polyurethane power battery potting adhesive and a preparation method and application thereof. The polyurethane potting adhesive is lightweight, has excellent comprehensive performance, and has a simple and controllable preparation process, is environmentally friendly and reliable, and has low cost. It can improve the stability and safety of power batteries, promote the development of new energy vehicles, and adapt to environmental protection requirements.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive comprises the following steps:

[0009] Step 1: Take 100 parts of polytetrahydrofuran diol and 56.31 parts of diphenylmethane diisocyanate by mass, put them into a reaction kettle at 80° C., and stir to react for 4 to 5 hours to obtain a polyurethane prepolymer;

[0010] Step 2: 100 parts of the polyurethane prepolymer prepared in step 1, 0.1-0.3 parts of bismuth zinc catalyst, 0.1-0.3 parts of silicone foaming agent, 0-0.25 parts of water, and 7.57-10.09 parts of 1,4-butanediol are added into a reaction kettle by mass, and stirred at room temperature for 5-10 minutes to obtain a polyurethane potting slurry.

[0011] The present invention also has the following technical features:

[0012] Preferably, the mean molecular weight of the polytetrahydrofuran diol is 2000.

[0013] Preferably, the molar ratio of elemental bismuth to zinc in the bismuth-zinc catalyst is 1:3.

[0014] Preferably, the stirring speed of the stirrer during the stirring process in step 1 and step 2 is 180 r / min.

[0015] The present invention also protects a lightweight energy-absorbing polyurethane power battery potting adhesive prepared by the method as described above and its application in a power battery. The polyurethane potting adhesive slurry is poured into the gap of a power battery pack, and then matured at a temperature of 20 to 40° C. for 7 to 8 days to obtain a sealed power battery pack.

[0016] Compared with the prior art, the present invention has the following technical effects:

[0017] The process of the present invention uses liquid MDI and polytetramethylene glycol (PTMG-2000) as raw materials to prepare a polyurethane prepolymer with a terminal isocyanate group, and then uses the prepolymer to react with 1,4-butanediol (BDO) by adjusting the chain extension coefficient to generate microporous foamed polyurethane to prepare a polyurethane power battery potting glue. A microporous structure is formed by reaction, and the polyurethane power battery potting glue is produced by a reaction molding process. According to the required foaming volume, the chain extension coefficient is adjusted for pouring to achieve the purpose of lightweight, so as to meet the relevant performance requirements of the power battery potting glue such as lightweight and energy absorption. The process synthesizes the prepolymer and adopts different chain extension coefficients to adjust the porosity, the size of the pores, and the degree of crosslinking, so as to adjust the performance of the polyurethane power battery potting glue. The process has high controllability, and compared with the wet coagulation process, the same foaming effect is achieved, and the wet process process, plant and equipment are less than the ordinary wet process, and the process is stable; the foaming volume is adjusted by controlling the chain extension coefficient, the amount of slurry used can be reduced, the cost is reduced, and it is suitable for large-scale production;

[0018] In the production process of the present invention, H2O is used as a foaming agent, no solvent is used, and no solvent pollution is generated, which is an environmentally friendly process; there is no solvent residue in the product, which is a green product; a solvent-free system is adopted, there is no pollution, and the solvent-free polyurethane can meet various safety and environmental protection indicators; no solvent vapor is emitted in the process, no water vapor is emitted, and even very little heat is emitted, which truly achieves zero emission; in order to improve the stability and safety of power batteries, promote the development of new energy vehicles, and meet environmental protection requirements,

[0019] The polyurethane potting adhesive prepared by the invention has the advantages of light weight, excellent energy absorption and shock absorption performance, mechanical property, thermal stability and bonding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart of the preparation of the lightweight energy-absorbing polyurethane power battery potting adhesive and the power battery potting process;

[0021] Figure 2 The cross-sectional SEM images of the polyurethane power battery potting adhesive of Examples 1-6 are as follows: (a) 75%; 80%; 85%; 90%; 95%; 100%. DETAILED DESCRIPTION

[0022] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0023] In the following embodiments, polytetrahydrofuran diol adopts PTMG-2000, and the number-average molecular weight is 2000, and the manufacturer is Chongqing Chiyuan Chemical Co., Ltd. (Chongqing, China);

[0024] MDI-50 was selected as diphenylmethane diisocyanate, and the manufacturer was Wanhua Chemical Group Co., Ltd. (Yantai, China);

[0025] The bismuth-zinc catalyst used was PC-02, produced by Yantai Sunshine Plastics Co., Ltd. (Yantai, China), and the molar ratio of bismuth to zinc in the bismuth-zinc catalyst was 1:3;

[0026] The silicone foam leveling agent used was Sicare-2003, produced by Guangzhou Siluoke New Materials Co., Ltd. (Guangzhou, China).

[0027] In the following examples, the speed of the stirrer in the reactor during the stirring reaction was 180 r / min.

[0028] Example 1

[0029] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0030] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0031] Step 2: 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth-zinc catalyst, 0.2 parts of silicone foaming agent, and 10.09 parts of 1,4-butanediol are added to a reaction kettle by mass and stirred at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0032] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 8 days to obtain a sealed power battery pack.

[0033] Example 2

[0034] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0035] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0036] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth zinc catalyst, 0.2 parts of silicone foaming agent, 0.05 parts of water, and 9.59 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0037] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 8 days to obtain a sealed power battery pack.

[0038] Example 3

[0039] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0040] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0041] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth zinc catalyst, 0.2 parts of silicone foaming agent, 0.10 parts of water, and 9.08 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0042] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 8 days to obtain a sealed power battery pack.

[0043] Example 4

[0044] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0045] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0046] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth zinc catalyst, 0.2 parts of silicone foaming agent, 0.15 parts of water, and 8.58 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0047] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 8 days to obtain a sealed power battery pack.

[0048] Example 5

[0049] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0050] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0051] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth zinc catalyst, 0.2 parts of silicone foaming agent, 0.2 parts of water, and 8.07 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0052] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 8 days to obtain a sealed power battery pack.

[0053] Example 6

[0054] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0055] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by weight, put them into a reactor at 80°C, stir and react for 5 hours to obtain a polyurethane prepolymer;

[0056] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.2 parts of bismuth zinc catalyst, 0.2 parts of silicone foaming agent, 0.25 parts of water, and 7.57 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 10 minutes to obtain a polyurethane potting slurry.

[0057] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 25°C for 7 days to obtain a sealed power battery pack.

[0058] Example 7

[0059] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0060] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reaction kettle at 80°C, stir and react for 4 hours to obtain a polyurethane prepolymer;

[0061] Step 2: Take 100 parts of the polyurethane prepolymer prepared in step 1, 0.3 parts of bismuth zinc catalyst, 0.3 parts of silicone foaming agent, 0.25 parts of water, and 7.57 parts of 1,4-butanediol, by mass, and put them into a reaction kettle, stir at room temperature for 8 minutes to obtain a polyurethane potting slurry.

[0062] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 20°C for 8 days to obtain a sealed power battery pack.

[0063] Example 8

[0064] The present embodiment provides a method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, comprising the following steps:

[0065] Step 1: Take 100 parts of PTMG-2000 and 56.31 parts of MDI-50 by mass, put them into a reactor at 80°C, stir and react for 4.5 hours to obtain a polyurethane prepolymer;

[0066] Step 2: 100 parts of the polyurethane prepolymer prepared in step 1, 0.1 parts of bismuth zinc catalyst, 0.1 parts of silicone foaming agent, 0.25 parts of water, and 7.57 parts of 1,4-butanediol are added to the reaction kettle by mass, and stirred at room temperature for 5 minutes to obtain a polyurethane potting slurry.

[0067] The prepared slurry is poured into the gaps of the power battery pack; then it is aged at 40°C for 7.5 days to obtain a sealed power battery pack.

[0068] Figure 1 The present invention is a flow chart of the preparation of the lightweight energy-absorbing polyurethane power battery potting adhesive and the power battery potting process;

[0069] Figure 2 The cross-sectional SEM images of the polyurethane power battery potting adhesive of Examples 1-6 are as follows: (a) 75%; 80%; 85%; 90%; 95%; 100%. Figure 2 It can be seen that with the increase of chain extension coefficient, the number of cells in the cross section of polyurethane power battery potting glue gradually decreases, and the cell density decreases. This phenomenon is mainly because the NCO group in the prepolymer is reduced, the CO2 produced by the reaction with the added H2O and H2O in the air is reduced, and the number of cells produced by molding is reduced. When the curing coefficient of PPBSs is 90%, 95%, and 100%, the cells in the cross section of PPBSs are relatively sparse and the cross-sectional surface is relatively smooth. When the curing coefficient of the potting glue is 75%, 80%, and 85%, the cells are closed or semi-open, spherical, and the cell distribution is relatively uniform and dense.

[0070] Table 3 shows the performance test results of polyurethane power battery potting glue with different chain extension coefficients prepared in Examples 1-6;

[0071] Table 3 shows the performance of polyurethane power battery potting glue with different chain extension coefficients prepared in Examples 1-6

[0072]

[0073] It can be seen from Table 3 that the tensile strength increases with the increase of the chain extension coefficient, and the elongation at break shows a downward trend. The tensile strength of PPBS with a chain extension coefficient of 85% is 3.45MPa, and the elongation at break is 480.18%. The hardness range of PPBSs is 47HA-57HA, which has moderate hardness and can provide a certain high elasticity. Taking the potting glue with a chain extension coefficient of 85% as an example, when PPBSs is compressed by 50%, the compressive stress is 1.89MPa. With the change of the chain extension coefficient, the foaming volume of the potting glue will change, and it can be adjusted to achieve the effect of lightweighting. The hysteresis energy density of the potting glue with a loading strain of 50% is 2.470J / m 3 , has a relatively high ability to resist external damage, thereby protecting the power battery. The potting glue has a high bonding strength to 304 steel. The maximum lap shear force of the potting glue with a chain extension coefficient of 85% and the 304 steel substrate is 744.59N, and the lap shear strength is 2.38MPa. The maximum lap shear force of the potting glue with a chain extension coefficient of 85% and the PET film substrate is 278.10N, and the lap shear strength is 0.89MPa.

[0074] The samples of Examples 1-6 were subjected to TGA tests. The results showed that all samples had little mass loss below 260°C, indicating that polyurethane power battery potting adhesives with different chain extension coefficients all exhibited high thermal stability and could ensure protection of the power battery during use.

[0075] By adjusting the chain extension coefficient, the potting compound exhibits excellent comprehensive performance and becomes an effective solution to solve the energy absorption and lightweight of power battery sealants. The potting compound can provide good mechanical properties, thermal stability and adhesion properties, and the preparation process is environmentally friendly and reliable, which has great prospects in power battery applications.

[0076] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the present invention.

Claims

1. A method for preparing a lightweight energy-absorbing polyurethane power battery potting adhesive, characterized in that: The following steps are involved: Step 1: Take 100 parts of polytetrahydrofuran diol and 56.31 parts of diphenylmethane diisocyanate by mass, put them into a reaction kettle at 80° C., stir and react for 4 to 5 hours to obtain a polyurethane prepolymer; Step 2: 100 parts of the polyurethane prepolymer prepared in step 1, 0.1-0.3 parts of bismuth zinc catalyst, 0.1-0.3 parts of silicone foaming agent, 0-0.25 parts of water, and 7.57-10.09 parts of 1,4-butanediol are added into a reaction kettle by mass, and stirred at room temperature for 5-10 minutes to obtain a polyurethane potting slurry.

2. The method for preparing the lightweight energy-absorbing polyurethane power battery potting adhesive according to claim 1, characterized in that: The mean molecular weight of the polytetrahydrofuran diol is 2000.

3. The method for preparing the lightweight energy-absorbing polyurethane power battery potting adhesive according to claim 1, characterized in that: The molar ratio of the element bismuth to zinc in the bismuth-zinc catalyst is 1:

3.

4. The method for preparing the lightweight energy-absorbing polyurethane power battery potting adhesive according to claim 1, characterized in that: The stirring speed of the stirrer during the stirring process described in step 1 and step 2 is 180r / min.

5. A lightweight energy-absorbing polyurethane power battery potting adhesive prepared by the method according to any one of claims 1 to 4.

6. An application of the lightweight energy-absorbing polyurethane power battery potting adhesive as claimed in claim 5 in a power battery, characterized in that: The polyurethane potting slurry is poured into the gaps of the power battery pack, and then aged at a temperature of 20 to 40° C. for 7 to 8 days to obtain a sealed power battery pack.

Citation Information

Patent Citations

  • Organic silicon-polyurethane potting glue and preparation method thereof

    CN104277197A

  • Polytetrahydrofuran peotopanaxadiol polyurethane elastomer and preparing method and application thereof

    CN107325259A

  • Method for preparing polyurethane grinding pad by solvent-free blade coating method

    CN116693913A

  • Low-density high-performance heat-conducting structural adhesive for power battery and preparation method thereof

    CN118085793A

Cited By

  • Optical sensor package structure and electronic device

    US12388064B2

  • Optical sensor package structure and electronic device

    US20230246012A1